Central precocious puberty in Neurofibromatosis Type 1: A case study - Chowdhury, Prodipta; Hoque, Ahmad Monirul; Banu, Hurjahan; Sultana, Nusrat; Jahan, Sharmin; Hasanat, Muhammad Abul (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
The premature onset of secondary sexual characteristics defines precocious puberty (PP). Neurofibromatosis type 1 (NF1), an autosomal dominant genetic disorder, has been associated with a variety of systemic manifestations, including endocrinopathy like precocious puberty. In children with NF1, there is an increased risk of developing an optic chiasmal tumor, which is the primary cause of central precocious puberty (CPP) but not the only one. Here we present a case of CPP due to NF1. A 6-year 10-month-old boy presented to us with a growth spurt and premature appearance of secondary sexual characteristics with aggressive behavior, occasional headaches, hyperphagia, café-au-lait spots & a positive family history of nodular skin disease. During thorough evaluation, pubertal gonadotropin response was established after gonadotropin-releasing hormone (GnRH) stimulation and imaging studies revealed an optic pathway glioma. This known NF1 complication can disrupt hypothalamic-pituitary axis function and trigger hormonal imbalances; in this patient, it specifically affected the GnRH axis. Subsequently, the patient was managed with GnRH analog therapy while awaiting definitive management. J Assoc Clin Endocrinol Diabetol Bangladesh, January 2025;4(1): 43-47